New β-isatin aldehyde-N,N′-thiocarbohydrazones: preparation, spectroscopic studies and DFT approach to antioxidant characteristics - Yakan, Hasan; Bakır, Temel Kan; Çavuş, M. Serdar; Muğlu, Halit (Springer Science and Business Media LLC, 2020)
Five new Schiff bases of isatin and its derivatives were prepared from monothiocarbohydrazides and 5-chloro isatin. The chemical structures of the synthesized compounds were performed by 1H NMR, 13C NMR, and FT-IR spectroscopic techniques and elemental analysis. The in vitro antioxidant activities of all the products were determined by 1,1-Diphenyl-2-Picryl Hydrazyl free radical scavenging method. It also examined the antioxidant properties of the compounds based on quantum chemical calculations as well as supporting experimental spectroscopic data. Theoretical calculations carried out at B3LYP correlation functional with 6-311++g(2d,2p) basis set. Some chemical reactivity descriptors obtained from AIM, NCI, and ELF analysis were used to reveal the relationship between the electronic and antioxidant properties of the compounds. Furthermore, the bond lengths, charge densities, potential energy densities, inter-atomic dipole moments, and delocalization indices of the active phenolic hydrogen bonds of the compounds were shown to be parameters that can be used to determine the antioxidant properties of compounds. New β-isatin aldehyde-N,N′-thiocarbohydrazones were synthesized. Structures of synthesized molecules were clarified using spectroscopic methods. Antioxidant activities of the compounds were tested by the DPPH method. AIM, NCI, and ELF analysis were performed to investigate the relationship between the electronic properties and antioxidant activity.
Keywords: 3. Good health